2020
DOI: 10.1148/ryai.2020190207
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Hierarchical Severity Staging of Anterior Cruciate Ligament Injuries from MRI

Abstract: This deep learning pipeline may lend towards diagnostic worklist prioritization, standardization, and generalizability in assessing anterior cruciate ligament lesions, in addition to point-of-care communication with patients by non-experts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…The 3D CNN models were not performed well as compared to 2D CNN due to the small dataset in the work of Namiri et al [ 39 ]. The model was found over-fitting in the case of partial tears, however obtained better results with 3D CNN than with 2D.The sample of patients were not balanced among all grading and dataset split based upon the patients, which caused correlations among multiple images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D CNN models were not performed well as compared to 2D CNN due to the small dataset in the work of Namiri et al [ 39 ]. The model was found over-fitting in the case of partial tears, however obtained better results with 3D CNN than with 2D.The sample of patients were not balanced among all grading and dataset split based upon the patients, which caused correlations among multiple images.…”
Section: Discussionmentioning
confidence: 99%
“…However, the burden of training the all three architectures, in a cascaded fashion, is computationally expensive and time consuming. In the study, Namiri et al [ 39 ] used 3D CNN classify hierarchical severity stages in ACL automatically, that had an accuracy 3% more than 2D CNN. The study of [ 40 ] related arthroscopy findings of MRI dataset and used DenseNet architecture upon 489 MRI samples only, in which 163 were from an ACL tear and 245 were from an intact ACL.…”
Section: Related Workmentioning
confidence: 99%
“…The sensitivity, specificity, and accuracy of MRI in the diagnosis of ACL injury was 96.78%, 90.62%, and 92.17%, respectively, and there was no great difference from the results of arthroscopy ( P > 0.05). Namiri et al [ 18 ] found that the indirect signs of ACL tear had high specificity (91%∼100%) and sensitivity in a retrospective study of the correlation between MRI imaging and arthroscopy in 100 patients. Therefore, these signs can determine whether the patient had an ACL tear, which was similar to the conclusion of this study, indicating that MRI can accurately diagnose ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…Right lower cut-out boxes represent a magnification of the left upper area (dashed box). In A and B: dark gray = Liu et al [3]; yellow = Germann et al [4]; blue = Namiri et al [14]; green = Bien et al [11]. In C: gray = Oei et al [18]; orange = Smith et al [20]; light blue = Phelan et al [21]; red = Crawford et al [19].…”
Section: Meniscus Tearsmentioning
confidence: 99%
“…The CNN achieved a sensitivity of 97-100% and a specificity of 100% for identifying ACL grafts. For intact ACL, the CNN sensitivities were 89-93% and specificities were 88-90%, whereas the CNN achieved sensitivities of 76-82% and specificities of 94-100% for full-thickness ACL tears [14]. The ground truth was based on radiological assessments, and comparisons to human readers were not reported.…”
Section: Introductionmentioning
confidence: 99%